Development of Electricity Program, Electrification Ratio with Human Development Index in West Java Province, Indonesia - Saepudin, Tete (International Journal of Energy Economics and Policy, 2018)
This research analyzes the development of rural electricity program, electrification ratio with human development index in West Java Province. The method used in this analysis is analytical descriptive with the aim of developer of rural electric program in an effort to increase the achievement of electrification ratio and human development index. Acceleration of the achievement of electrification ratio in West Java Province can exceed the national electrification ratio after the issuance of Regulation no. 21 Year 2014, on the implementation of electricity. The components of the human development index are formed from life expectancy, average length of schooling, school life expectancy, and per capita expenditure. Human development index, shows an increasing value although still below the average index of national human development (Indonesia). The results of the electrification ratio have a positive and significant effect on human development index. Keywords: Rural Electricity Program, Electrification Ratio, Human Development Index, West Java Province. JEL Classifications: O15, Q4